Strategi Orang Tua dengan Peran Ganda dalam Membentuk Karakter Anak - Rantri Mustika Dewi (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Parents are the first and main education in the family. The role of parents that can be carried out is by educating, nurturing and raising them until they become adults. In this case, parents have a very important role and parents are the first and main teachers for education and shaping children’s character. As a single parent, you have to play multiple roles to ensure the continuity of your family’s life. Single parents must be able to combine work and taking care of children well. This research method uses qualitative methods. The subjects in this research were parents with dual roles and children studying at Sanggar Bhineka, Sukoharjo Regency. The results of this research are that the dual role parental strategy in shaping children’s character occurs well where children’s manners and manners are formed very well.